Can the Smoke-Free Ratio be a Novel Indicator of the Cardiovascular and Metabolic Risk Reduction of Former Smokers? A Cross-Sectional Study - Dagcioglu, Basri Furkan (Puerto Rico Health Sciences Journal, 2023)
Objective: The association of smoking with many diseases is well known, as well as are the benefits of smoking cessation. While mentioning these benefits, the duration that passes after quitting smoking is always stressed. However, former smokers’ history of smoking exposure is usually ignored. This study aimed to investigate the possible effect of the pack-years history on several cardiovascular health parameters. Methods: A cross-sectional study was conducted on 160 ex smoker participants. A novel index was described and named the “smoke-free ratio” (SFR), which is the number of smoke-free years divided by the number of pack-years. The associations between the SFR and various laboratory values, as well as anthropometric and vital measurements, were investigated. Results: The SFR was negatively correlated with body mass index, diastolic blood pressure, and pulse in women with diabetes. In the healthy sub-group, fasting plasma glucose was negatively and high-density lipoprotein cholesterol positively correlated with the SFR. A Mann–Whitney U test revealed that the cohort with metabolic syndrome had significantly lower SFR scores (Z = -2.11; P = .035). In binary grouping, the participants with low SFR scores had higher rates of metabolic syndrome. Discussion: This study revealed some impressive features about the SFR, which is proposed as a novel tool for estimating metabolic and cardiovascular risk reduction in former smokers. Nevertheless, the actual clinical significance of this entity remains unclear.